Development of Augmented Reality-Based Learning Media with GeoGebra 3D to Enhance Interest and Concept Understanding in Ceva Theorem - Sarah, Siti; Simanjuntak, Rosi Ade Putri; Sinurat, Putra Paulus; Berutu, Jhosua; Suwanto, Fevi Rahmawati (Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to develop an Augmented Reality (AR)-based learning media utilizing GeoGebra 3D to teach the Ceva's Theorem in a triangular prism, with the goal of enhancing students' conceptual understanding and interest in learning mathematics. The research employs a Research and Development (R&D) approach using the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques involved media validation sheets, content validation sheets, practicality questionnaires, concept understanding tests, and student interest questionnaires. The validation results indicated that the developed media was highly valid, with an average score of 4.62 for technological design and 4.54 for content. The practicality of the media was also rated very practical by both teachers (4.7) and students (4.58). The effectiveness test revealed a significant improvement in concept understanding, with a gain value of 0.59 (moderate category), as well as an increase in student interest, reflected by an average score of 4.32 (high category). These findings indicate that the AR-based learning media using GeoGebra 3D is not only valid and practical but also effective in improving students' understanding and interest in complex spatial geometry topics. This study contributes to the development of interactive, contextual, and digital learning innovations that align with the demands of 21st-century education.